Spousal loss in Türkiye: Gendered grief and post-traumatic growth - Küsmez, Burak; Turhan, Zeynep; Kaçmaz, Sıla (Routledge, 2026)
This study explores the grief experiences of 16 women following spousal loss using interpretative phenomenological analysis. Findings show that grief is shaped not only as an individual trauma but also by gendered norms, caregiving roles, and structural inequalities. Three themes emerged: (1) living with unfinished and overwhelming loss, (2) gendered experiences of loss, and (3) surviving and rebuilding the self. Grief was often suppressed or postponed, becoming a chronic burden embedded in daily life. Children, economic hardship, and limited social support complicated the grieving process. Widowhood was shaped by stigma, honor-related concerns, and pressure to remarry, while women simultaneously carried sole caregiving responsibilities and were expected to “stay strong,” producing a form of necessary resilience. Drawing on the post-traumatic growth model, intersectionality, and feminist affect theory, the study argues that women’s narratives of strength arise less from voluntary transformation than from structural and social constraints. © 2026 Taylor & Francis Group, LLC.